The impact of the emoTICare program on socioemotional adjustment and psychological well-being in adolescents with type 1 diabetes mellitus - Martín-Ávila, Javier; Rodríguez-Jiménez, Esther; Valero-Moreno, Selene; Gil-Gómez, José Antonio; Montoya-Castilla, Inmaculada; Pérez-Marín, Marián (Frontiers in Endocrinology, 2025)
IntroductionType 1 diabetes mellitus (T1DM) is a chronic disease that can affect the emotional well-being and quality of life of adolescents. This group faces psychosocial and emotional challenges in addition to disease management, making it essential to improve psychological adjustment, emotional regulation, and social skills. The study aimed to explore psychosocial and emotional characteristics of adolescents with T1DM to justify psychological interventions, and to implement a serious game called emoTICare to promote clinical and socioemotional health indicators through a technological platform with artificial intelligence. The hypothesis proposed that adolescents would improve clinical and socioemotional indicators after following the emoTICare program.MethodThe design was quasi-experimental, single group, pre-post. Seventy-three participants were enrolled, and the final pilot sample comprised 44 Panamanian adolescents with T1DM, 64.4% female. Assessments occurred at baseline (T1), after 6 weeks without intervention (T2), and after the 6-week emoTICare intervention (T3), measuring health-related quality of life (HRQoL), disease threat perception, psychopathology, social skills, resilience, self-concept, and emotional awareness. Analyses included repeated measures (ANOVA and Friedman’s Test), comparative tests (Student’s t-test, Mann–Whitney U), correlational analyses, and descriptive statistics.ResultsThe initial assessment showed adolescents with high perception of disease threat and reduced quality of life. Boys reported greater physical (p <.01, d=.859), psychological and academic well-being (p <.05), and more adaptive problem-solving (p <.01). After the emoTICare intervention, we observed a significant reduction in perceived illness threat (p <.01, ηp²=.145) and improvement in verbal exchange of emotions (p <.01, W=.117). There was also a tendency toward improvements in resilience, self-concept, social skills, and adaptive coping scores.DiscussionFindings highlight psychosocial vulnerabilities of adolescents with T1DM and show the positive effects of emoTICare, particularly in reducing perceived disease threat. The program demonstrates potential as a useful tool for promoting health education and psycho-emotional skills.Clinical trial registrationClinicalTrials.gov, identifier EmoTICare NCT06331429.